2009
DOI: 10.1111/j.1745-4565.2009.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biogenic Amines Formation by Proteolytic Enterococci Strains Isolated From Raw Dromedary Milks From Southern Algeria

Abstract: Twenty-three strains of lactic acid enterococci isolated from dromedary raw milks in Southern Algeria were investigated for their proteolytic activity and ability to produce biogenic amines by decarboxylating amino acids: histidine, tyrosine and ornithine. All strains tested displayed proteolytic activities, but none of them were able to produce detectable biogenic amines in the usual adequate laboratory media, namely, Joosten and Northolt medium and Leuschner medium. Polymerase chain reaction experiments indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
3
1
Order By: Relevance
“…In addition, the average pH value observed was found to be slightly higher than that (4.9-7.3) reported previously by Tsai et al (2007). Since the optimum pH for biogenic amine production is slightly acidic (Hassaïne, Zadi-Karam, & Karam, 2009), however, it seems clear that there may be no apparent relationships among the data, including the amounts of biogenic amines and pH values, obtained in the present and previous studies. Thus, together with the fact that Natto is usually produced by fermentation within a 1-day period, and shipped and stored at freezing temperatures until consumed, it can be suggested that the large variations of biogenic amine contents in Natto products might be poorly influenced by the physicochemical properties, such as pH and water activity.…”
Section: Physicochemical Parameters In Nattocontrasting
confidence: 65%
“…In addition, the average pH value observed was found to be slightly higher than that (4.9-7.3) reported previously by Tsai et al (2007). Since the optimum pH for biogenic amine production is slightly acidic (Hassaïne, Zadi-Karam, & Karam, 2009), however, it seems clear that there may be no apparent relationships among the data, including the amounts of biogenic amines and pH values, obtained in the present and previous studies. Thus, together with the fact that Natto is usually produced by fermentation within a 1-day period, and shipped and stored at freezing temperatures until consumed, it can be suggested that the large variations of biogenic amine contents in Natto products might be poorly influenced by the physicochemical properties, such as pH and water activity.…”
Section: Physicochemical Parameters In Nattocontrasting
confidence: 65%
“…paracasei LGM31, LGM32, LGM35 showed a faster and stronger acidification ability, higher than that reported for others Algerian milk isolates (Bousmahamarroki et al 2015). This capacity is crucial in cheese production, since a rapid acidification favours the coagulation and limits the growth of adventitious undesired microorganisms (Hassaïne et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction was carried out according to the method of Hassaïne et al [11]. Bacteria strains stored at −20° C were inoculated into nutriment broth (1.5 mL) for overnight incubation.…”
Section: Dna Extractionmentioning
confidence: 99%